Sign language interpreting and interpreter education directions for research and practice - Marschark, Marc.; Peterson, Rico.; Winston, Elizabeth A. (New York ; Oxford : Oxford University Press, 2005)
This text provides an overview of the field of sign language interpreting and interpreter education, including evaluation of the extent to which current practices are supported by research and will be of use both as a reference book and as a textbook for interpreter training programmes.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Interpreters for the deaf -- Training of -- United States; Sign language -- Study and teaching -- United States; Deaf -- Means of communication -- United States